Impact of Type 1 Diabetes Mellitus on Skeletal Integrity and Strength in Adolescents as Assessed by HRpQCT. (2nd November 2020) - Devaraja, Janani; Jacques, Richard; Paggiosi, Margaret; Clark, Carolyn; Dimitri, Paul
ABSTRACT: Adults with type 1 diabetes mellitus (T1DM) are at risk of premature osteoporosis and fractures. The onset of T1DM typically starts during childhood and adolescence. Thus, the effects of DM on the skeleton may be established during this period. Studies in children with T1DM primarily use DXA with conflicting results. We present the first study in adolescents assessing the impact of T1DM on skeletal microstructure and strength using HRpQCT. We recruited 22 patients aged 12 to 16 years with T1DM who were matched by age, gender, and pubertal stage with healthy controls. Paired t tests were applied to assess differences in cortical and trabecular microarchitecture measurements from HRpQCT, and skeletal strength from HRpQCT‐derived microfinite element analysis. Subtotal body, lumbar, and pelvic parameters were assessed using DXA. There was no significant difference in subtotal body, lumbar spine, and pelvic BMD between T1DM and control pairs. However, tibial trabecular thickness was lower (−0.005 mm; 95% CI, −0.01 to −0.001; p = 0.029) and trabecular loading was lower at the distal radius (ratio of the load taken by the trabecular bone in relation to the total load at the distal end (Tb.F/TF) distal: −6.2; 95% CI, −12.4 to −0.03; p = 0.049), and distal and proximal tibia (Tb.F/TF distal: −5.2, 95% CI, −9.2 to −1.2; p = 0.013; and Tb.F/TF proximal: −5.0, 95% CI, −9.8 to −0.1; p = 0.047) in T1DM patients. A subanalysis of radial data of participants with duration of T1DM of at least 2 years and their matched controls demonstrated a reduced trabecular bone number (−0.15, 95% CI, −0.26 to −0.04; p = 0.012), increased trabecular separation (0.041 mm, 95% CI, 0.009–0.072; p = 0.015), an increased trabecular inhomogeneity (0.018, 95% CI, 0.003–0.034; p = 0.021). Regression models demonstrated a reduction in tibial stiffness (−0.877 kN/mm; p = 0.03) and tibial failure load (−0.044 kN; p = 0.03) with higher HbA1C. Thus, in adolescents with T1DM, detrimental changes are seen in tibial and radial microarchitecture and tibial and radial strength before changes in DXA occur and may result from poor diabetic control. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.